An empirical analysis of changes in the relative timeliness of issuer-paid vs. investor-paid ratings - Berwart, Erik; Guidolin, Massimo; Milidonis, Andreas (Journal of Corporate Finance, 2019)
We investigate the lead-lag relationships between issuer-paid and investor-paid credit rating agencies (CRAs), after the regulatory reforms in the U.S. (2002–2006) also including outlooks. Over our sample period, ratings (but not outlooks) issued by issuer-paid agencies were certified by the SEC while investor-paid agencies were not certified at all. First, in the wake of the reforms, we find a weaker lead effect of investor-paid over issuer-paid CRAs: after 2002, causality turned bi-directional. Second, after the overhaul of the rating business, issuer-paid CRAs behave less conservatively when dealing with outlook changes than with rating changes, which is consistent with a more conservative approach to ratings than to outlooks, because of the effects of the SEC's certification. Third, investor-paid downgrades become associated with more negative, statistically significant abnormal stock returns, than issuer-paid downgrades are. These results support the hypothesis that issuer-paid CRAs improved the timeliness of their ratings because of the recently implemented, tighter regulations. However, differences in abnormal returns imply that investor-paid rating actions still carry superior information. Adding data from the post NRSRO status acquisition by Egan Jones Ratings, the investor-paid agency studied in our paper, does not radically affect our results and confirms that some of the previously observed differences in timeliness and market impact have been fading over time.